Mengembangkan Kegiatan Menganyam Untuk Meningkatkan Motorik Halus Anak Usia 4-5 Tahun: Studi Kasus Di Desa Mekar Sari Gerung Tahun 2020 - Silvia Hernawati Putri; I Made Suwasa Astawa; Ika Rachmayani; I Nyoman Suarta (Indonesian Journal of Elementary and Childhood Education, 2021)
This research was motivated by the results of observations made during the Covid-19 pandemic while still paying attention to the applicable health protocols in Mekar Sari Gerung Village, Gerung Utara District, West Lombok Regency, found fine motor development in the weaving activities of children aged 4-5 years at school only. Using a single weaving technique, and producing only the form of woven mats, so that the child's fine motor development becomes less honed and developed. However, in this study the researchers tried to make a different shape from the usual form such as a mat, with a different shape. The purpose of this research is to look anywhere and steps to weave that can improve the fine motor skills of children aged 4-5 years in Mekar Sari Gerung Village, Gerung Utara District, West Lombok Regency in 2020. This research is a descriptive qualitative case study. The number of subjects in this study were 3 children. The data method used is the method of observation and documentation. The results of this study indicate an increase in fine motor skills through weaving activities for children aged 4-5 years (Case study) in Mekar Sari Gerung Village, 2020 in the first stage of development observation, the lowest proportion of 39.50% of children began to develop, while the proportion obtained by children was 51, 79% of children developed according to expectations (BSH). In phase II development, observation the lowest proportion obtained by children was as much as 88.09% according to expectations (BSB), developing the highest proportion obtained by children according to expectations (BSB). So, it can be denied that changing shapes, houses, fish, bags, clouds can improve the fine motor skills of children aged 4-5 years by giving different shape motifs.